Performance comparison of BPL, EtherLoop and SHDSL technology performance on existing pilot cable circuits under the presence of induced voltage - Che Y.X.; Ong H.S.; Lai L.C.; Karuppiah S.; Ong X.J.; Do N.Q. (Institute of Physics Publishing, 2023)
Pilot cable is originally used for utility protection. Then, pilot cable is further utilized for SCADA communication with low frequency PSK modem in the early 1990. However, the quality of pilot cable communication drops recently. Pilot cable starts to deteriorate due to aging and other unknown factors. It is also believed that the presence of induced voltage causes interference to existing modem communication which operates at low frequency channel. Therefore, BPL (Broadband Power Line), EtherLoop and SHDSL (Symmetrical High-speed Digital Subscriber Line) modem technology are proposed as alternative communication solutions for pilot cable communication. The performance of the 3 selected technologies on existing pilot cable circuits under the presence of induced voltage are measured and compared. Total of 11 pilot circuits with different length and level of induced voltage influence are selected for modem testing. The performance of BPL, EtherLoop and SHDSL modem technology are measured by the delay, bandwidth, packet loss and the long term usability SCADA (Supervisory Control and Data Acquisition) application. The testing results are presented and discussed in this paper. The results show that the 3 selected technologies are dependent on distance and independent on the level of induced voltage. Published under licence by IOP Publishing Ltd.